Identification of two novel variants of the BCL11B gene in two Chinese pedigrees associated with neurodevelopmental disorders - Che, Fengyu; Tie, Xiaoling; Lei, Hong; Zhang, Xi; Duan, Mingyue; Zhang, Liyu; Yang, Ying (Frontiers in Molecular Neuroscience, 2022)
Objective: The mutation of the transcription factor gene BCL11B has recently been reported to be associated with the development of neurodevelopmental disorders and immune deficiency. By analyzing the clinical features and genetic variations, this study aims to reveal the genetic etiology of four patients with neurodevelopmental disorders from two unrelated Chinese pedigrees. Methods: For the 4 cases, the clinical data were collected. Possibly pathogenic gene variations were analyzed by based-trio whole exome sequencing (Trio-WES) and validated by Sanger sequencing in their individual pedigree. Both in-vitro minigene assay and NMD assay were further used to evaluate the impact of splicing and frameshift variants. Results: The 4 patients showed mild to severe intellectual developmental disorder, accompanying with speech delay, dysmorphic facies and serious caries. In addition, the extended phenotype of developmental regression was seen in the proband from family 1, which wasn’t reported previously. Molecular analysis detected two novel heterozygous variants in BCL11B gene: a maternal splicing variant c.427+1G>A in family 1 and a de novo frameshift variant c.2461_2462insGAGCCACACCGGCG (p.Glu821Glyfs*28) in family 2. The in-vitro minigene assay revealed that the c.427+1G>A variant activated a new cryptic splice site. Overexpression assay confirmed that there was no significant difference in the mRNA and protein expression between the mutate-BCL11B (p.Glu821Glyfs*28) and the wild type. Hence, this finding confirmed that p.Glu821Glyfs*28 variant could be a NMD escaping variant. Conclusion: We report the extended phenotype of BCL11B-related disorders and revealed the clinical and genetic heterogeneity of the disease. The study firstly identified a splicing variant and a novel frameshift variant of BCL11B gene and confirmed its aberrant translation. Our findings expand the mutation spectrum of genetic the BCL11B gene which supports the clinical understanding of the associated neurodevelopmental disorders, and provide scientific evidence on diagnosis and genetic counseling for future patients.